Remittances and income smoothing - Catalina Amuedo-Dorantes; Susan Pozo (Institute for the Study of Labor (IZA), 2011)
Due to inadequate savings and binding borrowing constraints, income volatility can make households in developing countries particularly susceptible to economic hardship. We examine the role of remittances in either alleviating or increasing household income volatility using Mexican household level data over the 2000 through 2008 period. We correct for reverse causality and endogeneity and find that while income smoothing does not appear to be the main motive for sending remittances in a non-negligible share of households, remittances do indeed smooth household income on average. Other variables surrounding income volatility are also considered and evaluated.
urn:nbn:de:101:1-201104133908
Keywords: F22; O15; O54; 330; remittances; income smoothing; Rücküberweisung (Migranten); Haushaltseinkommen; Volatilität; Schätzung; Mexiko